Interleukin-6 Induced Proliferation Is Attenuated by Transforming Growth Factor-β-Induced Signaling in Human Hepatocellular Carcinoma Cells - Srivastava, Abhilasha; Sharma, Harshita; Khanna, Simran; Sadhu Balasundaram, Tejasvini; Chowdhury, Shibasish; Chowdhury, Rajdeep; Mukherjee, Sudeshna (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is often associated with an inflammatory setting. A plethora of cytokines is secreted in this milieu actively contributing to progression of the disease, however, the extent of cytokine interaction and how it contributes to HCC development still remains an enigma. In this regard, our analysis of available patient derived data suggests that cytokines like, interleukin-6 (IL-6) and transforming growth factor beta (TGF-β) are enriched in HCC. We further analyzed the effect of these cytokines independently, or in combination on HCC cells. Importantly, IL-6 was found to induce a STAT-3-dependent proliferation, and mediate its pro-proliferative effects through activation and direct interaction with p65 subunit of NFkB. Alternatively, TGF-β was found to induce a SMAD-dependent induction of epithelial to mesenchymal transition (EMT) coupled to growth arrest in these cells. Interestingly, simultaneous addition of IL-6 and TGF-β failed to have a profound impact on EMT markers, but resulted in attenuation of IL-6-induced pro-proliferative effects. Analysis of the putative molecular mechanism revealed a decrease in IL-6 receptor (IL-6R) transcript levels, reduced expression of IL-6-induced STAT-3 and its nuclear localization upon addition of TGF-β along with IL-6. Consequently, a reduced p65 activation was also observed in combination treatment. Importantly, SMAD levels were unperturbed and the cells showed more TGF-β-like feature under combination treatment. Finally, we observed that TGF-β resulted in enrichment of repressive chromatin mark (H3K27me3) cuopled to growth arrest, while IL-6 induced an open chromatin signature (H3K4me3) associated with an enhanced expression of EZH2. Overall, we for the first time show that TGF-β attenuates IL-6-induced effects by regulating receptor level, downstream signalling and epigenome. Understanding the complex interactions between these cytokines, can be imperative to better understanding of the disease, and manipulation of cytokine balance can act as a prospective therapeutic strategy.